EVALUASI PENGGUNAAN EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) DI PONDOK PESANTREN DARUL AMIN PALANGKA RAYA - Muhammad Ramadhan; Triwid Syafarotun Najah; Slamet Riyadi (STKIP Pesisir Selatan, 2026)
This study aims to evaluate the use of the Education Management Information System (EMIS) at the Darul Amin Islamic Boarding School in Palangka Raya based on single-database indicators as well as the efficiency, effectiveness, and synergy of educational data management. The study employed a quantitative evaluative approach, with data collected via a questionnaire administered to 26 respondents comprising educators and administrative staff. Data analysis was conducted using SPSS 27 through Pearson’s validity test, Cronbach’s Alpha reliability test, and descriptive analysis. The results indicate that all instrument items are valid with significance levels below 0.05 and a Cronbach’s Alpha value of 0.943, indicating very high reliability. The average score for the single database indicator was 3.7, while the scores for the efficiency, effectiveness, and synergy indicators were 3.713. The results indicate that EMIS is capable of supporting integrated data management, improving administrative quality, accelerating data reporting, and strengthening coordination among educational units. The study concluded that the use of EMIS falls into the “very good” category, although improvements are still needed in the areas of human resources and technological infrastructure.